Ten Years of the Institute of International Politics and Economics in Prague (Czech Journal of International Relations, 1967)
The Czechoslovak Constitution for International Politics and Economics was established in 1957 and began its activities in the autumn of that year. In fact, it was about the end of a several-year process, because proposals for the establishment of a similar state appeared already in the early fifties, and some of them were discussed very seriously. The successes and failures of these plans created both certain experiences for the new state and were also proof of the great need for research a workplace that would scientifically deal with international relations, world politics and economy and Czechoslovak foreign policy.The establishment of the UMPE in 1957 is actually a living proof of how the institution was and is closely connected with the overall development of international relations. In the period of the Cold War, it was not so necessary to deal scientifically with international relations, when they were limited to the necessary minimum. That is why the proposals to establish the institute found only limited support. Only the overall easing of international tension in the mid-1950s created favorable conditions for the development of international relations and for scientific research into this issue.